Flüchtlinge: Opfer - Bedrohung - Helden Elektronische Ressource Zur politischen Imagination des Fremden (Bielefeld : transcript, 2017)
How the power of linguistic figures shapes sociopolitical debates becomes remarkably clear in contemporary discussions about refugees who are seeking safe harbor in Europe. Heidrun Friese looks into the controversial imaginations of refugees in our society: the figure of the